Prominent Crista Terminalis in a Fetus - Evong, YD (Images Paediatr Cardiol, 2018)
BACKGROUND: The crista terminalis is a normal cardiac structure located in the right atrium. It is not usually seen using standard view transthoracic echocardiography techniques, but on occasion, hypertrophy allows for easy visualization of this structure, which can be mistakenly labelled pathologic. CASE: We report the first known case of a prominent crista terminalis detected in a fetus. CONCLUSIONS: This case confirms the presence of a prominent crista terminalis in a developing fetus, a variant which was exclusively described in the pediatric and adult populations until now. Although a prominent crista terminalis is a benign variant, the correct identification of this structure has important diagnostic implications. This report aims to increase familiarity with the appearance of a prominent crista terminalis on both fetal echocardiography and newborn transthoracic echocardiography in hopes that this will aid in the correct diagnosis of this variant in the future.